2019
DOI: 10.1016/j.rbo.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Fratura proximal do fêmur e lesão vascular em adultos – Relato de caso

Abstract: ResumoComplicações vasculares no tratamento cirúrgico da fratura do quadril são raras. A depender da lesão arterial, pode ocorrer um grave sangramento intraoperatório ou formação de hematoma subagudo com desenvolvimento de pseudoaneurisma arterial. Na literatura, as complicações mais frequentes relatadas são a formação de grandes hematomas locais após osteossíntese com parafuso deslizante do quadril. O objetivo do presente relato foi demonstrar um caso de lesão arterial tardia após osteossíntese proximal do fê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Vascular injury could be compression with blood flow restriction, intimal flap injury with decreased distal flow, intimal or atherosclerotic plaque rupture resulting in arterial thrombosis or thromboembolism, or acute hemorrhage by laceration or transection, which produces a pseudoaneurysm or arteriovenous fistula. 3 Vascular lesions may be caused by fracture fragments, predominantly the diverted lesser trochanter. 2 Barquet et al demonstrated seven noniatrogenic lesions produced by lesser trochanter or other bone fragments, both in patients undergoing conservative treatment and in patients who underwent a surgical fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular injury could be compression with blood flow restriction, intimal flap injury with decreased distal flow, intimal or atherosclerotic plaque rupture resulting in arterial thrombosis or thromboembolism, or acute hemorrhage by laceration or transection, which produces a pseudoaneurysm or arteriovenous fistula. 3 Vascular lesions may be caused by fracture fragments, predominantly the diverted lesser trochanter. 2 Barquet et al demonstrated seven noniatrogenic lesions produced by lesser trochanter or other bone fragments, both in patients undergoing conservative treatment and in patients who underwent a surgical fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular compromise in this anatomical region can be caused by bone fragments formed either due to iatrogenic reasons or after fracture, intramedullary nail locking screws, drilling perforation, or movement of bone fragments during reduction. 3 Depending on the vessel wall defect, the lesion may cause a massive intraoperative bleeding or subacute hematoma formation with arterial pseudoaneurysm development. 3 We report a false aneurysm of a calcified atherosclerotic right superficial femoral artery (SFA) that was unrecognized by the orthopaedic surgeon, subsequent to subtrochanteric femur fracture with displaced lesser trochanteric fragment and uneventful stabilization with open reduction and internal fixation using a cephalomedullary nail.…”
Section: Introductionmentioning
confidence: 99%
“…The deep femoral artery is the most commonly affected branch in the upper part of the femur (about 78.31 %). Few cases occurred in superficial femoral vessels (10.84 %) [ 10 ]. The deep femoral artery is more susceptible to injury than the superficial artery because it is deep, fixed and immobile [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly injured artery is the deep femoral artery and its branches that count about 77–78 %. The superficial femoral artery lesion accounts for only 7–10 % of the cases [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation